Rancang Bangun Aplikasi Pembelajaran Berbasis Web dan Android dengan Presensi Digital dan Sistem Poin Menggunakan Metode Waterfall - Juzairi, Wardah; Suhendar, Agus (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The implementation of learning at SMAN 1 Kalibawang requires an efficient academic administration system to replace manual processes that potentially cause data inaccuracies and suboptimal management. This study designs and develops a web-based learning application for teachers and a Flutter-based mobile application for students using the Waterfall system development method. The system is equipped with features such as real-time digital attendance, material distribution, assignment and quiz submission, as well as a motivation mechanism through the integration of a Points System. The system design is modeled using UML (Use Case and Activity diagrams), supported by system Flowcharts. Functional testing using Black Box Testing on 10 scenarios showed a success rate of 100%. The implementation of this system is expected to streamline school administrative procedures while increasing student participation and self-motivation in the learning process.